PENERAPAN MODEL PEMBELAJARAN DEEP LEARNING BERBANTUAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA MATERI KATA BAKU SISWA KELAS III SD NAMIRA KRAKSAAN - Nur Maulida, Husna; Prastiwi Sri Wijayanti, Ribut; Hattarina, Shofia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Based on an initial analysis, several factors contribute to low student scores, primarily teacher-centered approaches that lack variety. This study aims to improve learning outcomes in Indonesian standard vocabulary for third-grade students at Namira Kraksaan Elementary School, Probolinggo, by employing a Deep Learning instructional model assisted by flashcards. This study addresses two research questions regarding the application of this model and its impact on student learning outcomes. Utilizing Classroom Action Research (CAR), the study was conducted over two cycles, each consisting of two sessions , with 24 third-grade students as subjects. The results indicate a significant improvement in student learning outcomes. Initial pre-test data showed that only 9 students (37.5%) mastered the material. Following Cycle I, mastery increased to 16 students (66.67%), which had not yet met the classical mastery standards. However, in Cycle II, achievement rose significantly to 23 students (95.83%) meeting the standards. In conclusion, the application of the Deep Learning model assisted by flashcards effectively improves the Indonesian language learning outcomes of third-grade students.